Genital infection by Chlamydia trachomatis in couples attending in conjugal sterility ambulatory - Marques, Carlos Alberto S; Menezes, Maria Luiza B; Coelho, Iara Maria G; Marques, Carlos Reinado C; Celestino, Leonardo C; Melo, Márcio C; Lima, Priscila R (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: the sexually transmitted infections are relatively frequent and are serious public health problem in almost all over the world. Amongthese, caused by Chlamydia trachomatis(CT) is one of the most prevalent and self index of complication for reproductive health. Objective:toinvestigate the occurrence of genital CT infection in couples that seek treatment for infertility and other possible associated factors. Methods:a crosssectional study was held with the participation of 100 recruited couples treated by the sterility ambulatory of the Gynecologic Clinic of the Agame-non Magalhães Hospital - Recife-PE. Both men and women were submitted to Polimerase Chain Reaction (PCR) testing; the men being sampled fortheir first urine and the women for material of their cervical canal. Results:CT genital infection was observed in 17 couples (9.0% of men and 10.0%of women). There was coinciding infection of both partners in two couples. There was neither relationship between CT infection and the variousgenitourinary complaints nor the basic causes of infertility. Conclusion:the rate of CT infection in infertile couples is high. The suggestion is toinclude routine screening in infertility clinics.